Global Interim Guidance on Coronavirus Disease 2019 (COVID-19) During Pregnancy and Puerperium From FIGO and Allied Partners: Information for Health Care Professionals. Issue 1 (24th March 2021) - Poon, L.C.; Yang, H.; Kapur, A.; Melamed, N.; Dao, B.; Divakar, H.; McIntyre, H.D.; Kihara, A.B.; Ayres-de-Campos, D.; Ferrazzi, E.M.; Di Renzo, G.C.; Hod, M.
Abstract : ( Int J Gynecol Obstet . 2020;149:273–286) The International Federation of Gynecology and Obstetrics (FIGO) recently issued guidelines for the management of all pregnant patients during the coronavirus disease 2019 (COVID-19) pandemic, including patients with COVID-19 infection and patients with exposure to the virus. These guidelines should be used along with local guidelines and guidelines from other appropriate organizations.